2010
DOI: 10.1111/j.1529-8817.2010.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

LOW GENETIC VARIABILITY OF SARGASSUM MUTICUM (PHAEOPHYCEAE) REVEALED BY A GLOBAL ANALYSIS OF NATIVE AND INTRODUCED POPULATIONS1

Abstract: Sargassum muticum (Yendo) Fensholt is one of the most well-known invasive species in the world. There have, however, been few genetic investigations on both its introduced and native populations. There are also some questions about the taxonomic status of this species. This study is the first to assess the genetic diversity of S. muticum on a global scale, by utilizing one marker each from the extranuclear genomes, namely, plastidial RUBISCO and mitochondrial TrnW_I spacers, as well as the nuclear internal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 86 publications
(168 reference statements)
0
23
0
Order By: Relevance
“…Among the three molecular markers used, Rub spacer showed lowest genetic variability that is comparable to that in other studies on Sargassum [2,36,39]. This showed that Rub spacer has low mutation rate and may not be suitable for phylogeographical studies of Sargassum .…”
Section: Discussionmentioning
confidence: 53%
“…Among the three molecular markers used, Rub spacer showed lowest genetic variability that is comparable to that in other studies on Sargassum [2,36,39]. This showed that Rub spacer has low mutation rate and may not be suitable for phylogeographical studies of Sargassum .…”
Section: Discussionmentioning
confidence: 53%
“…For example, Sargassum muticum is introduced to British Columbia, Canada, but is found in a wide range of habitats, including pristine areas (Cheang et al. ). With regards to Criterion 2, test area genetic diversity “pools” were compared with global genetic diversity “pools” where possible.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought to have been transported to Europe through the importation of the Japanese oyster Crassostrea gigas (Farnham et al 1973), with a recent study suggesting that the stock originated from Korea (Bae et al 2013). It now ranges from Norway to Portugal and the Mediterranean (Engelen et al 2008;Cheang et al 2010).…”
Section: Introductionmentioning
confidence: 96%